Cultural Meaning of Hamlet Names in Kejobong District, Purbalingga Regency - Pangestuti, Tri Yuli; Mardikantoro, Hari Bakti; Baehaqie, Imam (Universitas Negeri Semarang, 2023)
Culture, environment, and language come together to form a collaboration in various fields of life, including the naming of a region. The place naming system is a rule for giving names to an area at a certain time, this is also called toponymy. One of them is the naming of the Kecobong District which is in Purbalingga Regency, Central Java. The name of the hamlet in Kejobong District has a complex meaning including its origin, conditions in the field, religion, and socio-cultural development. Toponymy is almost always associated with the identity of the region, so there is a story or stories that accompany it. The purpose of this research is to describe the formation process, cultural meaning, and categorization of hamlet names in Kejobong District, Purbalingga Regency. The researcher used an ethnoliguistic theoretical and qualitative descriptive methodological approach. Data collection was carried out using listening and speaking techniques. The validity of the research data was obtained using the persistence of observation and triangulation techniques. The data obtained were then analyzed using the distribution and matching methods. The results of the research analysis are (1) the process of forming hamlet names in Kejobong District, Purbalingga Regency morphologically consists of affixation and composition, (2) hamlet names in Kejobong District, Purbalingga Regency which have cultural meaning are Kedarpan Hamlet, Paduraksa Hamlet, Bendingan Hamlet, Silumbung Hamlet, Pengempon Hamlet, Karangsari Hamlet, Makamdawa Hamlet, Kalgung Hamlet, and Totogan Hamlet, and (3) categorization of hamlet names in Kejobong District.